ChemInform Abstract: Ruthenium‐Catalyzed Synthesis of 5‐Amino‐1, 2, 3‐triazole‐4‐carboxylates for Triazole‐Based Scaffolds: Beyond the Dimroth Rearrangement. Issue 29 (July 2015) - Ferrini, Serena; Chandanshive, Jay Zumbar; Lena, Stefano; Comes Franchini, Mauro; Giannini, Giuseppe; Tafi, Andrea; Taddei, Maurizio
Abstract Some N‐Boc ynamides bearing a terminal ester or aryl group are treated with azides to produce the desired triazoles with complete regiocontrol.